2020
DOI: 10.1186/s43055-020-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI measurement of optic nerve sheath diameter using 3D driven equilibrium sequence as a non-invasive tool for the diagnosis of idiopathic intracranial hypertension

Abstract: Background: The idiopathic intracranial hypertension is a disease that is represented by high intracranial pressure of unknown reason. The visual disturbance presents the main medical problem of this syndrome. This study was conducted to assess the diagnostic value of the optic nerve sheath diameter (ONSD) measured using MRI 3D DRIVE in the diagnosis of idiopathic intracranial hypertension.Results: The mean value of the ONSD measured using 3D DRIVE sequence in the patient group (5.81 ± 0.33) was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(44 reference statements)
0
2
0
1
Order By: Relevance
“…Previous studies indicated a strong correlation between increased ONSD and radiologic findings with CT and MRI [ 6 , 9 , 39 , 40 ]. Patients diagnosed with increased ICP by CT or MRI had lower ONSDs on ultrasound (5.67 mm; 95% CI 5.44–5.91 mm and 5.43 mm; 95% CI 5.25–5.61 mm) than patients diagnosed with invasive ICP monitoring (6.04 mm; 95% CI 5.76–6.32 mm).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies indicated a strong correlation between increased ONSD and radiologic findings with CT and MRI [ 6 , 9 , 39 , 40 ]. Patients diagnosed with increased ICP by CT or MRI had lower ONSDs on ultrasound (5.67 mm; 95% CI 5.44–5.91 mm and 5.43 mm; 95% CI 5.25–5.61 mm) than patients diagnosed with invasive ICP monitoring (6.04 mm; 95% CI 5.76–6.32 mm).…”
Section: Discussionmentioning
confidence: 98%
“…Dalam hal ini, MRI memiliki keunggulan dibandingkan dengan USG dan CT scan, yakni dapat membedakan ukuran saraf optikus dan selubung saraf optikus (gambar 4). 13,16 Tetapi dalam pengukuran selubung saraf optikus, terdapat penelitian yang menyatakan bahwa pengukuran selubung saraf optikus dengan menggunakan USG, CT scan, ataupun MRI memiliki tingkat akurasi yang tidak jauh berbeda. 13,17…”
Section: Gambar 3 Pengukuran Selubung Saraf Optikus Dengan Menggunakunclassified
“…Raised ICP is seen frequently after a severe TBI [1], therefore early identification is critical to ensure timely and appropriate management [7]. To avoid complications of the ventriculostomy, the traditional and gold standard method of measuring ICP, non-invasive methods of estimating ICP are preferred whenever possible and optic nerve sheath diameter (ONSD) is increasingly utilized to indirectly assess ICP using ultrasonography [8], CT scan [9] and MRI [10]. On other hand, fewer studies were published studying the significance of brain CT-derived ONSD in the evaluation and grading of TBI.…”
Section: Introductionmentioning
confidence: 99%